Desa Wisata Trowulan (Jurnal Ilmiah Pariwisata, 2016)
Trowulan Tourism Village in the district of Mojokerto, East Java Province, is a residential area adjacent to the historic sites of the Majapahit Kingdom. As a region which is located in the former of empire capital which become the inspiration of Indonesia founding, the appeal of Trowulan Village Tourism very high.In terms of tourism products, Trowulan inherited many historic sites of Majapahit era. The development in terms of packaging through Village Tourism is important.This research uses descriptive qualitative method. The conclusion of this study are, first, the Trowulan Tourism Village developed a pattern of community based tourism, in which citizens become the main actors in the tourism activities. Second, packaging Trowulan Village Tourism through travel packages with the concept of experiential tourism that explores aspects of the history, culture. Third, community empowerment program of the government has been run, but the impact is less felt by the community.